The Halal Paradox: Strategies for Resilient Indonesian Food MSMEs - Lailatul Qadariyah; Sarkawi Sarkawi (Faculty of Islamic Economics and Business, Universitas Islam Negeri Ar-Raniry, 2023)
Despite the mandatory halal certification for Indonesian businesses, the anticipated benefits, such as increased product value or market share expansion, have not materialized for all enterprises. This study investigates the marketing challenges faced by halal-certified Micro, Small and Medium-sized Enterprises (MSMEs) in the Bangkalan Regency, Indonesia, focusing on the food sector. Employing a qualitative research design with a phenomenological interpretive approach, the study utilizes data collected through interviews and document analysis from 10 MSME informants. The findings reveal three primary factors hindering their marketing efforts. Firstly, the absence of a centralized platform or marketplace specifically for halal products restricts their reach and visibility. Secondly, the COVID-19 pandemic has disrupted consumer behavior and market dynamics, posing a common challenge for all MSMEs, including those in the halal food sector. Lastly, limited public awareness and understanding of halal certification results in reduced demand for halal products. These findings highlight the need for multi-pronged interventions to support halal-certified MSMEs. This includes establishing dedicated halal product marketplaces, providing pandemic relief measures tailored to MSMEs, and implementing awareness campaigns to educate the public about the significance of halal certification. This study offers valuable insights into the marketing challenges faced by halal-certified MSMEs in a specific Indonesian context. The proposed solutions can inform policy interventions and marketing strategies to empower halal-certified businesses and promote the halal food industry.==============================================================================================================ABSTRAK – Paradoks Halal: Strategi untuk Daya Tahan UMKM Makanan Indonesia. Meskipun sertifikasi halal menjadi kewajiban bagi pelaku usaha di Indonesia, manfaat yang diharapkan, seperti peningkatan nilai produk atau ekspansi pangsa pasar, belum dirasakan oleh semua perusahaan. Penelitian ini mengkaji tantangan pemasaran yang dihadapi oleh Usaha Mikro Kecil dan Menengah (UMKM) yang telah tersertifikasi halal di Kabupaten Bangkalan, Indonesia, khususnya sektor makanan. Data penelitian dikumpulkan melalui wawancara dan analisis dokumen dari 10 informan UMKM dan dianalisis dengan pendekatan interpretatif fenomenologis. Hasil penelitian menunjukkan ada tiga faktor utama yang menghambat upaya pemasaran mereka. Pertama, ketiadaan platform khusus yang dapat menampung dan memasarkan produk-produk halal. Kedua, efek negatif pandemi COVID-19 yang mengganggu perilaku konsumen dan dinamika pasar, termasuk yang berada di sektor makanan halal. Terakhir, rendahnya kesadaran masyarakat akan sertifikasi halal yang mempengaruhi permintaan akan produk halal. Hasil ini menggarisbawahi pentingnya kerjasama berbagai pihak dalam mendukung UMKM bersertifikasi halal, yang mencakup pembentukan pasar khusus produk halal, penyediaan bantuan pandemi yang terukur untuk UMKM, dan pelaksanaan diseminasi tentang sertifikasi halal untuk meningkatkan kesadaran masyarakat akan pentingnya sertifikasi halal. Kajian ini memberikan input yang sangat berharga tentang tantangan pemasaran yang dihadapi oleh UMKM yang tersertifikasi halal dalam konteks Indonesia. Hal ini dapat digunakan untuk intervensi kebijakan dan strategi pemasaran bagi pemberdayaan usaha yang tersertifikasi halal sekaligus mempromosikan industri makanan halal.